Political determinants of corporate governance : political context, corporate impact - Roe, Mark J. (Oxford ; New York : Oxford University Press, 2003)
In this work, Mark Roe uses statistical and qualitative analysis to explore the relationship between politics, history, and business organization.
Includes index.
Includes bibliographical references: p. 207-219.
oif 14/10/14; 24/03/15
Loans
Keywords: Corporate governance; Business and politics; Corporate governance